The Systemic Risk and Structural Evolution of China’s Green Energy Industry - Shengchao Ye, Xinmiao Zhou (Forest Chemicals Review, 2022)
In order to achieve the sustainable development goals, the Chinese government has elevated the development of green energy to the level of a national strategy and has encouraged multiple financial channels to support green energy development. The capital market, especially the stock market, has become the most important factor in promoting the development of the green energy industry. This paper focuses on the analysis of systemic risk in the green energy capital market by selecting 2725 sets of stock market data from China's Green Energy Industry and its sub-industries from 2010 to 2021. The systemic risk level of China's Green Energy Industry and its major sub-industries is investigated by calculating VaR using the FIGARCH model. On this basis, the risk correlation and dynamic evolution of the green energy industry and its sub-industries are investigated by further constructing a multivariate DCC-GARCH model. The study found that (1) the photovoltaic industry has the highest risk level but is followed closely by the wind power and nuclear power industries. It is no longer the most important source of risk for China's Green Energy Industry; (2) the wind power and nuclear power industries have the same level of risk and have replaced the photovoltaic industry as the most important source of risk for China's Green Energy Industry; (3) the hydropower industry has the lowest level of risk and is an important guarantee for the healthy development of China's Green Energy Industry. Finally, based on the results of this empirical study, this paper puts forward some countermeasures and suggestions for the development of green energy.